Microplastic in fresh water fish at Lubuk Yu river, Maran, Pahang / Siti Suhaila Harith, Nur Azira Raihan Rosdi and Fauziah Shahul Hamid - Harith, Siti Suhaila; Rosdi, Nur Azira Raihan; Hamid, Fauziah Shahul (Universiti Teknologi MARA Cawangan Pahang, 2021)
Contamination of the river by microplastics is a worldwide significant problem. More or less, it is questionable whether this microplastic has already affected the freshwater organisms. Therefore, this study aimed to determine freshwater fish biodiversity and determine the abundance, distribution, composition of microplastics in fish from Lubuk Yu river, Maran, Pahang. Sampling was done at two different locations; middle and downstream, once a month for two months. Fishes were caught and identified. Digestive gut of fish undergone digestion, density separation and filtration. Through inspection of particles; each was identified, counted, and sorted out into categories based on shape, colour, and size. A total of 32 fishes were caught which represented 8 species. The most abundance species caught were Barbonymus schwanenfeldii, Cyclocheilichthys apogon, Hampala macrolepidota and Rasbora einthovenii with composition of 18.75% each. Shannon index (E), Shannon's equitability (EH) for both locations; middle stream and downstream were 1.41, 0.55 and 1.74, 0.59 respectively. Out of the 8 species of fishes, only the samples from Hypsibarbus wetmorei and Rasbora einthovenii contained microplastics. Microplastic were found in filament form, with the size ranging between 1.01 mm and 2.00 mm and colours varied from blue, black and red. In conclusion, the study triggers an alarm that our freshwater fish biodiversity from Lubuk Yu river has already been exposed to microplastics.